Anatomical and biochemical studies of Spartium junceum infected by Xylella fastidiosa subsp. multiplex ST 87 - S. Falsini; C. Tani; G. Sambuco; A. Papini; P. Faraoni; S. Campigli; L. Ghelardini; G. Bleve; D. Rizzo; M. Ricciolini; I. Scarpelli; L. Drosera; et al. (Protoplasma, 2022)
Spartium junceum L. is a typical species of Mediterranean shrubland areas, also grown in gardens and parks as an ornamental. In recent years in Europe, S. junceum has been recurrently found to be infected by different subspecies and genotypes of the quarantine regulated bacterium Xylella fastidiosa (Xf). This work presents for the first time the anatomy of S. junceum plants that we found, by means of genetic and immunochemistry analysis, to be naturally infected by Xf subsp. multiplex ST87 (XfmST87) in Monte Argentario (Grosseto, Tuscany, Italy), a new outbreak area within the EU. Our anatomical observations showed that bacteria colonized exclusively the xylem conductive elements and moved horizontally to adjacent vessels through pits. Interestingly, a pink/violet matrix was observed with Toluidine blue staining in infected conduits indicating a high content of acidic polysaccharides. In particular, when this pink-staining matrix was observed, bacterial cells were either absent or degenerated, suggesting that the matrix was produced by the host plant as a defense response against bacterial spread. In addition, a blue-staining phenolic material was found in the vessels and, at high concentration, in the pits and inter-vessels. SEM micrographs confirmed that polysaccharide and phenolic components showed different structures, which appear to be related to two different morphologies: fibrillary and granular, respectively. Moreover, our LM observations revealed bacterial infection in xylem conductive elements of green shoots and leaves only, and not in those of other plant organs such as roots and flowers.